Ergonomics in Veterinary Surgery-Risk Assessment With Intraoperative Motion Tracking. (September 2018) - Asadi, Hamed; Browne, Samantha M.; Simons, Micha C.; Breur, Gert J.; Yu, Denny
Musculoskeletal pain and discomfort are common occupational hazards in surgery, but limited studies have quantified these discomforts in veterinary medicine, where surgeries are performed on large and small animals. The objective of this study is to assess the upper extremities of attending and assisting surgeons soft tissue and orthopaedic small animal surgeries. Inertial measurement units (IMUs) and workload surveys were used to assess the physical workloads. Findings showed that orthopaedic surgeons experienced higher perceived workload and was observed more often in demanding posture than soft tissue surgeons. These results provide understanding of surgeons' workload that can inform alterations of surgical work environments to reduce musculoskeletal pain and discomfort in the workplace.